Comparison of half- and standard-dose ticagrelor in Chinese patients with NSTE-ACS. (3rd July 2016) - Xue, H. J.; Shi, J.; Liu, B.; Wang, D. Y.; Dong, Z. X.; Guo, H.; Kong, Y. H.; Sheng, L.; Shao, Q.; Sun, D. H.; Zhang, L.; Pan, Y. J.; et al.
Abstract: Ticagrelor is a novel direct-acting P2Y12 receptor antagonist used for preventing atherothrombotic events in patients with acute coronary syndromes (ACS). The current recommended dose is 90 mg bid, but a low dose of ticagrelor has not been previously studied in Chinese ACS patients. Therefore, we performed this study to observe the different effects of half- and standard-dose ticagrelor on platelet aggregation in Chinese patients with NSTE-ACS. Sixty-two NSTE-ACS subjects were assigned to half-dose ticagrelor ( n = 20), standard-dose ticagrelor ( n = 22) and clopidogrel ( n = 20) groups. Five days after drug administration, VerifyNow P2Y12 assay was performed to test P2Y12 reaction units (PRU) and inhibition of platelet aggregation (IPA). High-platelet reactivity (HPR) was defined as a PRU > 208. The adverse events, including bleeding events and dyspnoea, were monitored throughout the study. PRU values in the half-dose (44.55 ± 32.88) and standard-dose (39.10 ± 40.02) ticagrelor were dramatically lower than those in the clopidogrel group (189.20 ± 65.22; P < 0.0001). The half-dose (84% ± 10%) and standard-dose (86% ± 13%) ticagrelor both showed greater IPA than clopidogrel (33% ± 20%; P < 0.0001). There were no significant differences in PRU and IPA between the two ticagrelor groups ( P = 0.3085 and 0.4028, respectively). HPR rates were significantly lower in the two ticagrelor groups (0% for both) than those in the clopidogrel group (35%). In conclusion, half-dose ticagrelor had a similar inhibitory effect on platelet aggregation as standard-dose ticagrelor in Chinese patients with NSTE-ACS, which was significantly stronger than that of clopidogrel.